2022
DOI: 10.1093/jn/nxac172
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Consumption of Sulfur Amino Acids and Risk of Diabetes: A Prospective Cohort Study

Abstract: Background Cross-sectional studies suggested that consumption of sulfur amino acids (SAAs) including methionine and cysteine is associated with a higher risk of type 2 diabetes (T2D) in humans and T2D-related biomarkers in animals. But, whether higher long-term SAA intake increases the risk of T2D in humans remains unknown. Objectives We aimed to investigate the association between long-term dietary SAA intake and risk of T2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…An additional limitation with the present study includes the relatively short study duration of 8 weeks. Lastly, the intake of SAA in the control group may be higher than a typical Western diet, however, relative to body weight the content it is in line with reported intake in upper quantile groups in large population studies including NHANES and the Framingham cohort studies 68 .…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…An additional limitation with the present study includes the relatively short study duration of 8 weeks. Lastly, the intake of SAA in the control group may be higher than a typical Western diet, however, relative to body weight the content it is in line with reported intake in upper quantile groups in large population studies including NHANES and the Framingham cohort studies 68 .…”
Section: Discussionsupporting
confidence: 73%
“…Methionine and cysteine are essential and semi-essential sulfur amino acids (SAA) with a FAO/WHO minimum (recommended) intake of 15 (19) mg/kg/d in adults 1 . High dietary intake and plasma concentrations of SAA are strongly and linearly related to increased risk of metabolic disease and development of obesity [2][3][4][5][6][7][8][9] . In a large population-based cohort study of men and women (n = 5179), the difference in fat mass between lower and upper percentiles of plasma total cysteine (tCys) was 11 kg 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two independent Dutch cohorts of men and women aged 40–74 y, plasma methionine was associated with liver fat, whereas tCys was associated with overall obesity [ 10 ]. Recent prospective cohort studies showed that plasma tCys was associated with diabetes risk [ 11 ], whereas an increased dietary intake of SAA was associated with increased cardiovascular risk scores, diabetes risk and diabetes-related mortality [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids other than BCAAs are also involved in glucose metabolism. Excess intake of sulfur amino acids (methionine and cysteine) is associated with a higher risk of diabetes in the US population [ 15 ], and histidine is negatively associated with glucose and insulin resistance in the Chinese population [ 16 ]. In diabetic rats, alanine and glutamine supplementation reduces and improves blood glucose levels [ 17 ].…”
Section: Introductionmentioning
confidence: 99%